Synthesis of Fluorocyclotriphosphazene Derivatives and Their Fire-Retardant Finishing on Cotton Fabrics. (30th June 2010) - Zhanxiong, Li; Liping, Du
Abstract : A series of novel fire-retardant agents, fluorocyclotriphosphazene derivatives with the substitution groups of 2, 2, 3, 3-tetrafluoropropoxy groups were synthesized using hexachlorocyclotriphosphazene and 2, 2, 3, 3-tetrafluoropropyl alcohol as starting materials. The synthesized fire-retardant agent was emulsified and applied on the cotton fabric finishing to reduce the flammability and afford water/oil repellency simultaneously. The optimum finishing process was achieved according to the test of cotton finishing with fluorocyclotriphosphazene. The treated cotton showed not only excellent fire-retardant performance, but also water and oil repellency with little change in strength and whiteness.